2012
DOI: 10.1186/1472-6963-12-417
|View full text |Cite
|
Sign up to set email alerts
|

Use of medical tourism for hip and knee surgery in osteoarthritis: a qualitative examination of distinctive attitudinal characteristics among Canadian patients

Abstract: BackgroundMedical tourism is the term that describes patients’ international travel with the intention of seeking medical treatment. Some medical tourists go abroad for orthopaedic surgeries, including hip and knee resurfacing and replacement. In this article we examine the findings of interviews with Canadian medical tourists who went abroad for such surgeries to determine what is distinctive about their attitudes when compared to existing qualitative research findings about patients’ decision-making in and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…This consisted of 144 people following TKA, and 134 following THA; four participants had other lower limb arthroplasty procedures. The cohort consisted of 104 men and 178 women with a mean age ranging from 59 years12 to 76 years 13. No studies reported the mean duration of pain symptoms and only Harding et al 14 reported the mean number of comorbidities in their cohort (2.8).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This consisted of 144 people following TKA, and 134 following THA; four participants had other lower limb arthroplasty procedures. The cohort consisted of 104 men and 178 women with a mean age ranging from 59 years12 to 76 years 13. No studies reported the mean duration of pain symptoms and only Harding et al 14 reported the mean number of comorbidities in their cohort (2.8).…”
Section: Resultsmentioning
confidence: 99%
“…No studies reported the mean duration of pain symptoms and only Harding et al 14 reported the mean number of comorbidities in their cohort (2.8). Three studies included patients who had previously undergone lower limb arthroplasty 12 15 16…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A crucial task is explaining these flows and the push or pull factors underlying them. There is growing empirical evidence in the wider literature about differing motivations (1,(12)(13)(14)(15), and how wordof-mouth information and clinical networks shape travel patterns. Considering the sample, why are patients predominantly Romanian?…”
Section: International Patientsmentioning
confidence: 99%